Belief in Protecting Others and Social Perceptions of Face Mask Wearing Were Associated With Frequent Mask Use in the Early Stages of the COVID Pandemic in the UK - Warnock-Parkes, Emma; Thew, Graham R.; Clark, David M. (Frontiers in Psychology, 2021)
Face masks are now seen as a key tool in the world’s recovery from the COVID-19 pandemic. However, during the early stages of the outbreak, face mask use in the United Kingdom (UK) was significantly lower than that of countries equally impacted by the virus. We were interested to explore whether social cognitions played a role in levels of mask wearing. A cross-sectional online survey of UK adults (n=908) was conducted in July 2020. Estimated face mask use and thoughts about wearing face masks were assessed using measures developed for this study. Participants also answered questions about their general mood, social anxiety and basic demographic data. Multiple regression was used to examine factors associated with mask wearing. Participants’ estimated mask wearing was low when in public spaces, such as the park (17%) or walking on the high street (36%). However, broadly fitting with UK guidance at the time, rates were considerably higher when in situations of closer proximity to others, such as on public transport (94%), in a shop or café (62%), when speaking to somebody in an enclosed public space (67%) or in a busy area when social distancing was not possible (79%). When looking at estimated mask wearing when in proximity to others, positive social cognitions (e.g., I’ll look confident and competent wearing a mask) were associated with more wearing, whereas negative social cognitions (e.g. I’ll look anxious, I’ll look foolish etc.) were associated with less wearing. These results remained after controlling for factors that have indicated increased risk from COVID-19 (age, gender, ethnicity, presence of a health condition or pregnancy), belief about the health benefit for others, and levels of depression and social anxiety. The largest predictors of mask wearing were the amount people believed wearing a mask would keep others safe and the presence of an underlying health condition. The study findings indicate that future public health campaigns would benefit from a focus on strengthening beliefs about the protective benefits of masks, but also promoting positive social messages about wearing in public (e.g. mask wearing means you are confident and competent).